Can useful biomarker information be obtained from museum fossil specimens treated with Paraloid® B-72 acrylic resin? - Luke M. Brosnan; Stephen F. Poropat; Madison Tripp; Sebastian Stanley; Peter Hopper; Xiao Sun; William D.A. Rickard; Antônio Á.F. Saraiva; Renan A.M. Bantim; Juliana M. Sayão; Alexander W.A. Kellner; Kliti Grice (Organic Geochemistry, 2025)

Fossilisation of Fish Soft Tissue in Oxidative Microniches of Anoxic Sediments - Amy L. Elson; Lorenz Schwark; Paul F. Greenwood; Madison Tripp; Alex I. Holman; Michael E. Böttcher; Peter Hopper; Robert H. C. Madden; Luke M. Brosnan; Jessica H. Whiteside; Stephen F. Poropat; Lance Grande; et al. (Environmental Microbiology, 2025)
Organic analyses of past organisms enhance our understanding of Earth's evolutionary history, complementing the macrofossil record. Biomolecular remains are typically vulnerable to diagenetic mineralisation, but can persist in exceptional depositional settings such as Lagerstätten. Their preservation is usually linked to anoxic conditions that exclude aerobic degraders. However, we report intact skin tissue of the fossil fish Diplomystus dentatus from the Fossil Basin Lagerstätte (USA), preserved through phosphate permineralisation in an oxygen‐enriched microenvironment. Notably, only the skin with scales retained tissue integrity, and this organic material was closely associated with fluorapatite absent from the surrounding matrix. Geochemical analyses revealed higher oxidation states in the skin than in vertebrae and bones, likely due to early degradation of the fatty acid‐rich dermis. Redox‐sensitive biomarkers and isotopic data (δ 15 N) indicated a less reducing environment in the skin region compared to bones and the eye, yet more reducing than the surrounding sediment. This localised oxygen enrichment fostered sulphide‐oxidising bacteria, evidenced by mineral sulphates (barite) found only in the skin. Phosphatisation was likely driven by dermal breakdown and the release of H+, reducing alkalinity and enabling phosphate mineralisation over the carbonate system.

Corrigendum to “Fire distinguishers: Refined interpretations of polycyclic aromatic hydrocarbons for paleo-applications” [Geochimica et Cosmochimica Acta 289 (2020) 93–113] - A. Tyler Karp; Alex I. Holman; Peter Hopper; Kliti Grice; Katherine H. Freeman (Geochimica et Cosmochimica Acta, 2025)

Protocols to assist deconvolution of co-eluting 5β– and 5α–steranes by gas chromatography–mass spectrometry - Luke M. Brosnan; Paul F. Greenwood; Peter Hopper; Kliti Grice (Organic Geochemistry, 2025)

A paleoenvironmental and ecological analysis of biomarkers from the Eocene Fossil Basin, Green River Formation, U.S.A. - Amy L. Elson; Lorenz Schwark; Jessica H. Whiteside; Peter Hopper; Stephen F. Poropat; Alex I. Holman; Kliti Grice (Organic Geochemistry, 2024)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Variation in plant diversity in mediterranean‐climate ecosystems: the role of climatic and topographical stability - Richard M. Cowling; Alastair J. Potts; Peter L. Bradshaw; Jonathan Colville; Margarita Arianoutsou; Simon Ferrier; Felix Forest; Nikolaos M. Fyllas; Stephen D. Hopper; Fernando Ojeda; Şerban Procheş; Rhian J. Smith; et al. (Journal of Biogeography, 2015)
Aim Although all five of the major mediterranean‐climate ecosystems ( MCE s) of the world are recognized as loci of high plant species diversity and endemism, they show considerable variation in regional‐scale richness. Here, we assess the role of stable Pleistocene climate and Cenozoic topography in explaining variation in regional richness of the globe's MCE s. We hypothesize that older, more climatically stable MCE s would support more species, because they have had more time for species to accumulate than MCE s that were historically subject to greater topographic upheavals and fluctuating climates. Location South‐western Africa (Cape), south‐western Australia, California, central Chile and the eastern (Greece) and western (Spain) Mediterranean Basin. Methods We estimated plant diversity for each MCE as the intercepts of species–area curves that are homogeneous in slope across all regions. We used two down‐scaled global circulation models of the Last Glacial Maximum ( LGM ) to quantify climate stability by comparing the change in the location of MCE s between the LGM and present. We quantified the Cenozoic topographic stability of each MCE by comparing contemporary topographic profiles with those present in the late Oligocene and the early Pliocene. Results The most diverse MCE s – Cape and Australia – had the highest Cenozoic environmental stability, and the least diverse – Chile and California – had the lowest stability. Main conclusions Variation in plant diversity in MCE s is likely to be a consequence not of differences in diversification rates, but rather the persistence of numerous pre‐Pliocene clades in the more stable MCE s. The extraordinary plant diversity of the Cape is a consequence of the combined effects of both mature and recent radiations, the latter associated with increased habitat heterogeneity produced by mild tectonic uplift in the Neogene.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Genes involved with folate uptake and distribution and their association with colorectal cancer risk - Jane C. Figueiredo; A. Joan Levine; Won H. Lee; David V. Conti; Jenny N. Poynter; Peter T. Campbell; David Duggan; Juan Pablo Lewinger; Maria Elena Martinez; Cornelia M. Ulrich; Polly Newcomb; John Potter; et al. (Cancer Causes & Control, 2010)

The cystic fibrosis transmembrane conductance regulator gene and ion channel function in patients with idiopathic pancreatitis - Michele D. Bishop; Steven D. Freedman; Julian Zielenski; Najma Ahmed; Annie Dupuis; Sheelagh Martin; Lynda Ellis; Julie Shea; Isobel Hopper; Mary Corey; Paul Kortan; Gregory Haber; et al. (Human Genetics, 2005)

Foods, nutrients and prostate cancer - Allison M. Hodge; Dallas R. English; Margaret R.E. McCredie; Gianluca Severi; Peter Boyle; John L. Hopper; Graham G. Giles (Cancer Causes & Control, 2004)

Evidence of two pathways for the metabolism of phenol by Aspergillus fumigatus - Kerina H. Jones; Peter W. Trudgill; David J. Hopper (Archives of Microbiology, 1995)

Evidence of two pathways for the metabolism of phenol by Aspergillus fumigatus - Kerina H. Jones; Peter W. Trudgill; D. J. Hopper (Archives of Microbiology, 1995)